Wittgenstein as a Gricean Intentionalist. Issue 1 (2nd January 2016) - Unnsteinsson, Elmar Geir
Abstract : According to the dominant view, the later Wittgenstein identified the meaning of an expression with its use in the language and vehemently rejected any kind of mentalism or intentionalism about linguistic meaning. I argue that the dominant view is wrong. The textual evidence, which has either been misunderstood or overlooked, indicates that at least since the Blue Book Wittgenstein thought speaker's intentions determine the contents of linguistic utterances. His remarks on use are only intended to emphasize the heterogeneity of natural language. Taking into account remarks written after he finished the Investigations, I show how Wittgenstein anticipated the basic tenets of Gricean intention-based semantics. These are, in particular, the distinction between 'natural' and 'non-natural' meaning and the distinction between what a speaker means by an utterance and what the expression uttered means in the speaker's natural language. Importantly, Wittgenstein also believed that only the meaning of the speaker determined the content of ambiguous expressions, such as 'bank', on a particular occasion of utterance